Metode Belajar Kelompok dalam Meningkatkan Aktifitas Belajar Siswa Kelas IX pada Mata Pelajaran Ekonomi di SMP Parigi Tangerang - Suharwanto (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
This paper contains Group Learning Methods in Improving Learning Activities of Class IX Students in Economics Subjects at SMP Parigi Tangerang. This paper focuses on Group Learning Methods in Improving Student Learning Activities. This study used the Classroom Action Research (PTK) method. The design of the designed research consists of and (a) action planning, (b) action implementation. (c) observation/reflection, and (d) follow-up action planning (Ministry of Education and Culture, 1999). The study population was grade IX students of SMP Parigi Pondok Aren, South Tangerang City. Sampling with random sampling system. The results showed that the selection or determination of friends in forming a study group was based on adjacent seats, Therapeutic skills developed when students studied together in groups looked good, Student learning activities during teaching and learning activities that applied group learning methods in Economics subjects showed an increase, Acquisition of student learning outcomes in Economics teaching and learning activities Those who applied the learning method together in groups showed significant improvement.